Determining the Influence of Sample Preparation and Feed Form on the Predictability of the Near Infrared Reflectance Spectroscopy Technique - Caitlin E. Evans; Nana S. Frempong; Thomas N. Nortey; Charles R. Stark; Chad B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2021)
The near infrared reflectance spectroscopy (NIRS) technique is a rapid and non-destructive technique used to evaluate the chemical composition of complete feed and ingredients. The accuracy of its prediction is not only affected by instrument calibrations but also by sample particle size, shape, and arrangement. The purpose of this study was to determine the effect sample preparation method and feed form (mash and pellet) have on the accuracy of the NIRS technique using standard calibrations provided with the instrument. The experiment was designed as a 3 × 2 factorial with three methods of analysis (laboratory, NIRS-ground, and NIRS-unground) and two feed forms (mash and pellet). All samples were evaluated for crude protein (CP) content. Prior to analysis, subsamples were ground through a 0.5 mm sieve for analysis by laboratory and NIRS-ground methodologies. Laboratory values from wet chemistry analyses were obtained using the Dumas Combustion method for comparison to results from the NIRS. Ground and unground samples were scanned on a Foss NIRS D2500 machine with a wavelength range of 400 to 2,500 nm at a reflectance of log (1/R) at 2 nm intervals for each sample. There was an interaction (P ≤ 0.05) observed between feed form and method of analysis. The CP content of unground feed samples varied for the feed forms, but the grinding samples yielded similar results for both NIRS and laboratory analyses. Analyzing unground feed samples using standard calibrations yielded less accurate results compared to the samples ground prior to analysis using either NIRS or laboratory methods.
Keywords: Chemical composition; Feed form; Near Infrared Spectroscopy; Prediction; Unground